The Effect of Online Training Through ERISE: On the Competence of Managing Letters in Yogyakarta Special Region Vocational School Teachers - Yuliansah; Sutirman; Dwihartanti, Muslikhah; Yeni Suyanto, Umar (Economic Education Analysis Journal, 2024)
This research is to find out whether there is a significant influence on online training management through Erise on the competencies of MPLB Vocational School teachers in the Special Region of Yogyakarta. This study uses an experimental method with a quantitative approach. The experimental design used is pre-experimental with one group pretest-posttest. Data collection in research using instrument tests, the sample of this study amounted to 26 people with purposive sample techniques. The results of this study are: (1) there is an increase in the results of the cognitive aspect training by 67.47%; (2) there is an increase in the mastery of the skills of participants in the management of letters through Erise; and (3) There are differences on line. Therefore, it can be concluded that online training in managing letters through Erise influences significantly on the competence of MPLB Vocational School teachers in the Special Region of Yogyakarta.